Effect of Class II HDAC inhibition on glutamate transporter expression and survival in SOD1-ALS mice. (24th August 2017) - Lapucci, Andrea; Cavone, Leonardo; Buonvicino, Daniela; Felici, Roberta; Gerace, Elisabetta; Zwergel, Clemens; Valente, Sergio; Mai, Antonello; Chiarugi, Alberto
Highlights: Class II HDAC inhibition increases EAAT2 transcripts in primary glial cultures. Class II HDAC inhibition restores EAAT2 expression in the spinal cord of SOD1 mice. Class II HDAC inhibition restores glutamate uptake in the spinal cord of SOD1 mice. Class II HDAC inhibition does not prolong survival of SOD1 transgenic mice. Abstract: Transcriptional deregulation emerges as a key pathogenetic mechanism in ALS pathogenesis, and non-class-specific histone deacetylase (HDACs) inhibitors proved of therapeutic efficacy in preclinical models of ALS. When tested in patients, however, these drugs failed, probably because of a lack of selectivity toward pathogenetic HDACs. Here, we studied the effects of MC1568, an inhibitor of Class-II HDACs which have been reported to contribute to ALS pathogenesis. We focused on transcriptional regulation of glutamate transporter EAAT2, whose reduced expression may contribute to motor neuron degeneration in ALS. We report that MC1568 highly increased EAAT2 transcripts in primary cultures of mouse glia, but these increases did not correlate with increased glutamate uptake capacity. Accordingly, we found that MC1568 augmented protein expression of EAAT2 together with its sumoylation, a post-translational modification typically altering protein function and localization. When tested in SOD1G93A mice, however, MC1568 fully restored the reduced spinal cord expression of EAAT2 and glutamate uptake up to control levels. A prolonged treatment with MC1568 (from onset to end stage) was unable to prolong survival of mice. Data reveal a key role of Class-II HDACs in expression and function of glutamate transporter, further corroborating preclinical and clinical evidence that the sole restoration of glutamate uptake is not of therapeutic relevance to ALS therapy.